2014
DOI: 10.5430/bmr.v3n2p31
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Responsibility in Ghana: An Overview of Aspects of the Regulatory Regime

Abstract: This paper examines some aspects of the regulatory regime affecting corporate social responsibility (CSR) in Ghana. It seeks to assess the relationship between law and the actions of corporate organisations and its implications for corporate responsibility in Ghana. Corporations are critical actors in the political, economic, -social and cultural development of all countries. Besides providing goods and services, they are a source of livelihood for many and contribute to government revenue through the payment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…These outcomes are in line with [37], who concluded that a business entity that can make a strong claim to business ethics and or corporate social responsible human rights, employee rights, stakeholder rights, environmental protection, community relations, transparency, environmental stewardship and sustainability principles is the Oil and Gas industry. [66], collaborates this assertion and noted that MOCs are active and play leadership roles in developing good corporate practices and codes of conduct in the work place and engagement with different facets of society in which they operate.…”
Section: Mocs's Csr Activities and Practicesmentioning
confidence: 71%
See 2 more Smart Citations
“…These outcomes are in line with [37], who concluded that a business entity that can make a strong claim to business ethics and or corporate social responsible human rights, employee rights, stakeholder rights, environmental protection, community relations, transparency, environmental stewardship and sustainability principles is the Oil and Gas industry. [66], collaborates this assertion and noted that MOCs are active and play leadership roles in developing good corporate practices and codes of conduct in the work place and engagement with different facets of society in which they operate.…”
Section: Mocs's Csr Activities and Practicesmentioning
confidence: 71%
“…The relationship between YP and CSRIV, and YP and TAST are both negative (r = -0.2967 and r= -0.2788 respectively). Among the independent variables (TAST, CSRIV, CSRDC), however, there was no signi cant correlation among the variables, an indication that no multi-collinearity issues exist, and based on [66], the regression estimates are accepted to be accurate. In uence of CSR disclosure on nancial performance was assessed using the model estimation analysis to provide empirical evidence of the effects of CSR investment and disclosure on the nancial sustainability of MOCs operating in Africa.…”
Section: Descriptive Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…They also state that while governments in developing countries may require lower levels of CSR, MNCs may decide to pursue some level of CSR activities, thereby annulling the obligation of governments' need to interfere and enforce mandatory ethical actions. Although there are some laws regarding CSR in Ghana, these laws are not enforced by regulatory agencies, thereby leading to CSR mostly being a voluntary action [77].…”
Section: Discussionmentioning
confidence: 99%
“…A value of two means absence of autocorrelation and values less than or greater than two means the presence positive or negative autocorrelation among independent variables. The result for the Durbin-Watson test was 1.9, implying that the speci ed model for the analysis did not violate the independent residuals assumptions [58,66,67,68] and there was no collinearity problem among the predictor variables.…”
Section: Effect Of Csr and Csr Disclosure On Financial Performancementioning
confidence: 97%